The disappearance of Eleanor Rigby [videorecording (DVD)] - Benson, Ned; McAvoy, James, 1979-; Chastain, Jessica, 1977-; Hader, Bill, 1978-; Davis, Viola, 1965- ([Publisher not identified], 2015)
Once happily married, Connor and Eleanor suddenly find themselves as strangers longing to understand each other in the wake of tragedy. The film explores the couple's story as they try to reclaim the life and love they once knew and pick up the pieces of a past that may be too far gone.